Desiderata for digital consent in genomic research. - Parra-Calderón, CL; Kaye, J; Moreno-Conde, A; Teare, HJA; Nuñez-Benjumea, F (Springer, 2018)
Herein, we describe the characterization of a Digital Consent (DC) System to support current ethical-legal issues associated with challenges posed by informed consent for genomic research. A potential solution to support ongoing interaction with patients and allow control over how their data and samples are being used in genomic research can be Digital Consent based. But there are other challenges that need to be addressed, such as incidental findings when analyzing the results of genomic tests (not expected). This paper addresses security and privacy recommendations for the development of precision medicine, and the interoperability references of Health Information Standardization Organizations such as HL7 and IHE, as well as recent research in the field of ethics in Genomic Medicine. As a result of this work, ten key features that need to be further explored have been identified in order to support the realization of DC in Genomic Research.